11p13 deletion, Wilms' tumour, and aniridia: unusual genetic, non-ocular and ocular features of three cases. Issue 9 (September 1990) - Jotterand, V; Boisjoly, H M; Harnois, C; Bigonesse, P; Laframboise, R; Gagné, R; St-Pierre, A
Abstract : Three cases of Wilms' tumour and sporadic aniridia were followed up for periods ranging from 32 months to seven years. All had a deletion of the short arm of the eleventh chromosome 11p13, including one case with mosaicism, a cytogenetic feature that has not been previously described in the Wilms' tumour and sporadic aniridia association. Unusual non-ocular features found in all patients included tracheomalacia and delayed closure of the anterior fontanelle. In two cases tracheomalacia was responsible for respiratory distress after general anaesthesia. Wilms' tumour developed bilaterally in one patient and on the isthmus of a horseshoe kidney in another patient. In addition to the more commonly observed ocular features the presence of a corneal pannus was noted before 38 months of age in all patients and as early as 17 months in one case. An iridocorneal adherence with an overlying corneal opacity (presumably related to abnormal developmental cleavage of the anterior segment) was noted in one eye only of the mosaicism case.